The New Paradigm of Merdeka Curriculum: Implementation of Pancasila Education Subject in Elementary School - Fransiska Faberta Kencana Sari; Sukarno; Tri Murwaningsih (International Journal of Elementary Education, 2023)
This research is motivated by the implementation of a new curriculum for elementary schools in Indonesia, namely the Merdeka Curriculum. The Merdeka Curriculum brings changes to educational standards in elementary schools. Pancasila education is compulsory, and learning with the New Paradigm is the standard process for elementary education. This study aims to analyses about the intervention process carried out by schools in terms of implementing Pancasila Education subjects with the Merdeka Curriculum. This research was conducted through a qualitative design with a case study approach. The subjects of this study were teachers of the first batch of schools that implemented the Merdeka Curriculum. The sample selection used the purposive sampling method. Data collection techniques using interviews, observation and documentation studies. The validity of the data was obtained through a source, technique and time triangulation. Data analysis was performed using the Creswell qualitative data analysis technique with the NVivo program. The implementation results cover eight aspects: diagnostic assessment, differentiated learning, discussion and collaboration, character building, learning projects, learning resources based on information and communication technology, formative and summative assessments. This study concludes that the implementation of Pancasila Education Subject has followed the standard process of the New Paradigm Merdeka Curriculum. The suggestion from this study is to improve teacher skills in applying a more varied differentiated approach and conducting formative assessments through process assessment to optimize the implementation of the Merdeka Curriculum in the Pancasila Education subject.